2020
DOI: 10.3390/v13010007
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Phage in Combination with Staphylococcus epidermidis as a Potential Treatment for Staphylococcus aureus-Associated Atopic Dermatitis and Suppressor of Phage-Resistant Mutants

Abstract: Atopic dermatitis is accompanied by the abnormal overgrowth of Staphylococcus aureus, a common cause of skin infections and an opportunistic pathogen. Although administration of antibiotics is effective against S. aureus, the resulting reduction in healthy microbiota and the emergence of drug-resistant bacteria are of concern. We propose that phage therapy can be an effective strategy to treat atopic dermatitis without perturbing the microbiota structure. In this study, we examined whether the S. aureus phage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
1
25
0
4
Order By: Relevance
“…aureus-specific phages and phage lysins constitute another group of medicines with a potential for use in AD. A recent study showed that a treatment with S. epidermidis and SaGU1, a S. aureus phage, showed a sustained inhibition of S. aureus growth [162]. The ongoing research on Staphefekt, an engineered bacteriophage endolysin showing a specific bactericidal activity towards S. aureus, might confirm the clinical efficacy of this approach in AD treatment [163].…”
Section: Therapeutic Methods With the Potential Of Restoring The Normal Skin Microbiotamentioning
confidence: 96%
“…aureus-specific phages and phage lysins constitute another group of medicines with a potential for use in AD. A recent study showed that a treatment with S. epidermidis and SaGU1, a S. aureus phage, showed a sustained inhibition of S. aureus growth [162]. The ongoing research on Staphefekt, an engineered bacteriophage endolysin showing a specific bactericidal activity towards S. aureus, might confirm the clinical efficacy of this approach in AD treatment [163].…”
Section: Therapeutic Methods With the Potential Of Restoring The Normal Skin Microbiotamentioning
confidence: 96%
“…159 SaGU1 has also been shown to significantly decrease SA levels in vitro and in AD-like mouse models while also decreasing epidermal thickening characterized by histopathology in mice. 160 Bacteriophage pSa-3, combined with a surfactant to promote dissociation of SA aggregates, significantly decreased the aggregation of SA in vitro and cutaneous bacterial load in AD-like mouse models. 161 Staphefekt SA.100, a recombinant endolysin produced by bacteriophages, has been successfully used to treat SA folliculitis in three cases.…”
Section: Bacteriophagesmentioning
confidence: 96%
“…46 Taken together, these findings have unlocked the therapeutic potential of commensal microbes and have led to many clinical trials using commensal microbes in the treatment of inflammatory skin diseases. [47][48][49] For instance, in a recent phase I/II clinical trial, topical application of Roseomonas mucosa was determined to be safe and effective in adults and paediatric patients with AD, lowering the steroid hormone requirement and decreasing the S. aureus burden in skin. 50 Similarly, a phase I trial of topical application of S. hominis (A9 strain) isolated from healthy skin effectively lowered S. aureus colonization in patients with AD.…”
Section: Commensal Microbes Limit the Growth Of Skin Pathogensmentioning
confidence: 99%